Central Amygdala Prepronociceptin-Expressing Neurons Mediate Palatable Food Consumption and Reward - Hardaway, J. Andrew (Neuron, 2019)
Food palatability is one of many factors that drives food consumption, and the hedonic drive to feed is a key contributor to obesity and binge eating. In this study, we identified a population of prepronociceptin-expressing cells in the central amygdala (Pnoc(CeA)) that are activated by palatable food consumption. Ablation or chemogenetic inhibition of these cells reduces palatable food consumption. Additionally, ablation of Pnoc(CeA) cells reduces high-fat-diet-driven increases in bodyweight and adiposity. Pnoc(CeA) neurons project to the ventral bed nucleus of the stria terminalis (vBNST), parabrachial nucleus (PBN), and nucleus of the solitary tract (NTS), and activation of cell bodies in the central amygdala (CeA) or axons in the vBNST, PBN, and NTS produces reward behavior but did not promote feeding of palatable food. These data suggest that the Pnoc(CeA) network is necessary for promoting the reinforcing and rewarding properties of palatable food, but activation of this network itself is not sufficient to promote feeding.